2018
DOI: 10.14440/jbm.2018.244
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of a cell-based assay to discover agonists of the nuclear receptor REV-ERBα

Abstract: The nuclear receptors are transcription factors involved in the regulation of a variety of physiological processes whose activity can be modulated by binding to relevant small molecule ligands. Their dysfunction has been shown to play a role in disease states such as diabetes, cancer, inflammatory diseases, and hormonal resistance ailments, which makes them interesting targets for drug discovery. The nuclear receptor REV-ERBα is involved in regulating the circadian rhythm and metabolism. Its natural ligand is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Compound 24 showed a high selectivity over 20 nuclear receptors, which can reverse the degradation of REV-ERBa protein mediated by inflammatory stimuli. Subsequently, Gul et al 76 established a mammalian cell-based two-hybrid assay system and found compound 25 as a novel agonist of REV-ERB. In addition, three other compounds against REV-ERB, compounds 26-28 (Figure 4), were found using this method.…”
Section: Modulators For Rev-erbsmentioning
confidence: 99%
“…Compound 24 showed a high selectivity over 20 nuclear receptors, which can reverse the degradation of REV-ERBa protein mediated by inflammatory stimuli. Subsequently, Gul et al 76 established a mammalian cell-based two-hybrid assay system and found compound 25 as a novel agonist of REV-ERB. In addition, three other compounds against REV-ERB, compounds 26-28 (Figure 4), were found using this method.…”
Section: Modulators For Rev-erbsmentioning
confidence: 99%
“…Heme binding to REV-ERBα ( K d 2–4 µM, ref. 15 ) is prevented by mutating H602 into F ( 16 ). REV-ERBα H602F displayed a decreased transcriptional repressive activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2014 N/A pSG5-GAL4(DBD)-hPXR(LBD) Lemaire et al. 2006 N/A pM (Gal4 empty) Clontech Cat# PT3119-5 pGAL4-hCAR1 Hering et al. 2018 N/A p(UAS) 4 -tk-SEAP This article N/A p-RL (CMV) [renilla luciferase normalization vector] Promega Cat# E2261 p-EGFP-hCAR1 GeneCopoeia Cat# EX-A0964-M29 pGal4-Rev-erbα Hering et al.…”
Section: Key Resources Tablementioning
confidence: 99%
“…Finally, to minimize off-target detection effects, we describe the use of mammalian one- (or two-) hybrid systems. For complete details on the use and execution of this protocol, please refer to Hering et al. (2018) .…”
mentioning
confidence: 99%
See 1 more Smart Citation